Tau Imaging: Use and Implementation in New Diagnostic and Therapeutic Paradigms for Alzheimer’s Disease - Alexandra Gogola; Brian J. Lopresti; Davneet S. Minhas; Oscar Lopez; Ann Cohen; Victor L. Villemagne (Geriatrics)
Alzheimer’s disease (AD) affects an estimated 6.9 million older adults in the United States and is projected to impact as many as 13.8 million people by 2060. As studies continue to search for ways to combat the development and progression of AD, it is imperative to ensure that confident diagnoses can be made before the onset of severe clinical symptoms and new therapies can be evaluated effectively. Tau positron emission tomography (PET) has emerged as one method that may be capable of both, given its ability to recognize the presence of tau, a primary pathologic hallmark of AD; its usefulness in determining the spatial distribution of tau, which is necessary for differentiating AD from other tauopathies; and its association with measures of cognition. This review aims to evaluate the scope of tau PET’s utility in clinical trials and practice. Firstly, the potential of using tau PET for differential diagnoses, distinguishing AD from other dementias, is considered. Next, the value of tau PET as a tool for staging disease progression is investigated. Finally, tau PET as a prognostic method for identifying the individuals most at risk of cognitive decline and, therefore, most in need of, and likely to benefit from, intervention, is discussed.